[Late Night at Reykjavik] - Streng, Evelyn Fiedler (1975)
Photograph of 10:20 PM at Reykjavik from the University of Iceland. The blurry photograph depicts part of the city past a lake surrounded by dark trees. The city is full of small, colorful buildings in rows surrounding a church with a pointed roof to the left. The church roof is wide and stands tall above the city. A street stretches across the bottom of the photograph.